발달심리학적 관점에서 본 영유아 심리평가 도구: 초기 부모-자녀 관계 평가를 위한 관찰 접근법 - 박한선(Hanson Park), 최정원(Jungwon Choi) (Singyŏng chŏngsin ŭihak, 2025)
This paper focuses on psychological assessment tools employing observation-based methods and supplementary instruments to evaluate early parent-child interactions. Direct observation techniques objectively assess the qualitative aspects of parent-child interactions, such as parental sensitivity, emotional responsiveness, and overall dyadic interaction quality, thus providing insights that complement parent-based assessments. Despite their valuable objectivity, observation-based tools are resource intensive, require specialized expertise, and must be culturally adapted. This review emphasizes the integration of various assessment approaches into a multidimensional framework, facilitating the precise identification of early relationship issues and the formulation of effective intervention strategies. This paper highlights the pressing need for standardizing these tools within the Korean context. KCI Citation Count: 0